2021
DOI: 10.1177/20406207211017788
|View full text |Cite
|
Sign up to set email alerts
|

The role of axicabtagene ciloleucel as a treatment option for patients with follicular/marginal zone lymphoma

Abstract: Chimeric antigen receptor (CAR) T-cell therapy with axicabtagene ciloleucel (axi-cel) continues to make its way in the treatment of B-cell lymphomas. Follicular lymphoma (FL) is the second most common non-Hodgkin’s lymphoma. While its prognosis is usually good, the disease is considered incurable and patients still relapse. High-risk subgroups such as high FLIPI score or early relapses (POD24) face poor outcomes. Current treatment options with phosphatidylinositol 3-kinase (Pi3K) inhibitors or other novel agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 88 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…Axicabtagene ciloleucel (axi-cel) is approved for relapsed/refractory DLBCL and follicular lymphoma in adults. 13 In the initial phase 2, multicenter study axi-cel showed an overall response rate of 82%, complete response rate of 54% at 6 months, and an overall survival rate of 52% at 18 months. 14 Brexucabtagene autoleucel is approved for relapsed/refractory mantle cell lymphoma (MCL) and B-ALL.…”
Section: Overview Of Current Fda-approved Car T-cell Therapiesmentioning
confidence: 98%
“…Axicabtagene ciloleucel (axi-cel) is approved for relapsed/refractory DLBCL and follicular lymphoma in adults. 13 In the initial phase 2, multicenter study axi-cel showed an overall response rate of 82%, complete response rate of 54% at 6 months, and an overall survival rate of 52% at 18 months. 14 Brexucabtagene autoleucel is approved for relapsed/refractory mantle cell lymphoma (MCL) and B-ALL.…”
Section: Overview Of Current Fda-approved Car T-cell Therapiesmentioning
confidence: 98%
“…Yescarta (axicbtagene ciloleucel) is an anti-CD19 autologous CAR T cell that has an overall and complete rate of 83 and 58 percent, respectively, for the treatment of adult patients with relapsed or refractory large B cell lymphoma 25 and adult patients with relapsed or refractory follicular lymphoma (FL). 4 To manufacture Yescarta, autologous T cells are extracted and retrovirally engineered to express CAR with a murine anti-CD19 scFv coupled to CD28 and CD3-zeta costimulatory domains. The CRS (in all grades) was recorded in roughly 94 percent of patients treated with Yescarta, whereas a higher grade of CRS was seen in 13% of those controlled with tocilizumab and corticosteroid therapy.…”
Section: Car T Cell Therapy In Cancermentioning
confidence: 99%
“…1 This approach has indicated a remarkable outcome in the treatment of patients with paediatric acute lymphoblastic lymphoma (ALL) in addition to the treatment of other cancers, such as diffuse large B cell lymphoma (DLBCL), follicular lymphoma (FL), and multiple myeloma. [2][3][4][5][6] Due to the success of CAR T cell therapy in cancer, researchers were encouraged to extend its application to other diseases. Furthermore, as T cells are key players in tackling viral infections, such as infections caused by the human immunodeficiency virus (HIV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimeric antigen receptor (CAR)-T-cell therapy is a novel type of tumor immunotherapy that has improved outcomes for many patients with relapsed or refractory (R/R) lymphomas, showing varied efficacy in diffuse large B-cell lymphoma (DLBCL) (objective response rate (ORR) 52-88%; complete response (CR) 40-59% ( 3 ), mantle cell lymphoma (MCL) (CR 59%) ( 4 ), and chronic lymphocytic leukemia (CLL) (ORR 57-74%; CR 21%) ( 5 ). To date, several CAR-T-cell therapies have received FDA approval in the USA, including axicabtagene ciloleucel (axi-cel) ( 6 ) and lisocabtagene maraleucel (liso-cel) ( 7 ) for R/R DLBCL, axi-cel for R/R follicular lymphoma (FL) ( 8 ), and brexucabtagene autoleucel (brexu-cel) for R/R MCL and B-cell acute lymphoblastic leukemia (ALL) in adults ( 4 ). CAR-T-cell therapy has had a substantial impact on overall survival (OS) and progression-free survival (PFS), but it also comes with a host of adverse events (AEs), including cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS), which can lead to treatment failure ( 9 ).…”
Section: Introductionmentioning
confidence: 99%